Effects of nitrogen rate and cultivar on vegetative growth, yield and storability of onion (Allium cepa L.), River Nile State, Sudan - Elkashif, Mohamed; Ahmed, Hassan Abdelmotalib; Ali, Mohamed (Gezira Journal of Agricultural Science, 2018)
Onion is one of the most important vegetable crops in the Sudan. Nitrogen fertilization and cultivars are crucial factors for onion production and storability in the River Nile State. Therefore, the objective of this study was to determine the effects of nitrogen rate and cultivar on vegetative growth, yield and storability of onion ( Allium cepa L.) in the River Nile State, Sudan. Experiments were carried out at Shendi Research Station farm during two consecutive seasons of 2014/15 and 2015/16. Treatments consisted of three nitrogen rates, 0, 43 and 86 kg N ha -1 applied in the form of urea and two cultivars, Baftaim and Abufrewa. Treatments were arranged in a randomized complete block design with three replicates. Results showed that application of nitrogen at 86 kg N/ha significantly resulted in the most vigorous vegetative growth and the highest total yield for both cultivars in both seasons. However, the highest values of doubles and bolters were recorded for the highest nitrogen rate and the lowest values were recorded for the unfertilized control for both cultivars in both seasons. The cultivar Baftaim had more vigorous vegetative growth, larger bulb size and higher total yield than the local cultivar Abufrewa in both seasons. However, Abufrewa cultivar had higher dry matter content and better storability than Baftaim. The highest values of weight loss were recorded for Baftaim cultivar with the highest nitrogen rate (86 kg N/ha) and the lowest values were recorded for  unfertilized Abufrewa in both seasons. Application of nitrogen at the higher rate generally resulted in higher postharvest losses than the unfertilized control in both cultivars and seasons. It is recommended to apply 86 kg N/ha to both cultivars, grow Baftaim cultivar for immediate marketing and Abufrewa for long term storage. يعتبر البصل من اهم محاصيل الخضر في السودان . المعاملات الفلاحية مثل التسميد بالنيتروجين والاصناف تعتبر من العوامل الهامة جداً في انتاج وتخزين البصل في ولاية نهر النيل. هدفت الدراسة إلى معرفة تأثير التسميد بالنيتروجين والصنف علي النمو الخضري والإنتاجية والقدرة التخزينية للبصل. أجريت هذه التجربة بالمزرعة التجريبية بمحطة بحوث شندي ، ولاية نهر النيل في الموسمين 2014/15 و0152/16. اشتملت المعاملات علي ثلاثة معدلات من النتروجين وهى صفر و43 و86 كجم نتروجين للهكتار اضيفت في شكل يوريا مع صنفين من البصل وهى بافطيم و ابوفريوة.  استخدم تصميم القطاعات العشوائية الكاملة بثلاث مكررات. أظهرت النتائج أن اضافة النتروجين بمعدل 86 كجم للهكتار اعطى معنويا افضل نمو خضري وأعلى إنتاجية لكلا الصنفين من البصل وفى كلا الموسمين. ولكن اعلى معدلات الخلف والازهار المبكر كانت بإضافة أعلى معدل للنتروجين وادناها كانت للشاهد غير المسمد في كلا الموسمين. الصنف بافطيم اعطى افضل نمو خضري واكبر الابصال حجما واعلى انتاجية بالمقارنة مع الصنف المحلى ابوفريوة في كلا الموسمين. لكن الصنف أبوفريوة أعطى أعلى نسبه من المادة الجافة وأفضل قدرة تخزينية مقارنة بالصنف بافطيم. أعلى معدلات فقدان الوزن كانت للصنف بافطيم المسمد بالمعدل الاعلى للنتروجين وادناها كانت لابوفريوة غير المسمد في كلا الموسمين. اضافة النتروجين بالمعدل الأعلى اعطى أعلى فاقد ما بعد الحصاد بالمقارنة مع البصل غير المسمد في كلا الموسمين. يوصي بإضافة 86 كجم نتروجين للهكتار لكلى الصنفين وزراعة الصنف بافطيم للتسويق العاجل وزراعة ابوفريوة للتخزين طويل الأجل.